EFISIENSI ALOKATIF USAHATANI PADI ORGANIK LAHAN SAWAH DI KABUPATEN BANYUMAS - Kusmantoro Edy Sularso; Agus Sutanto; Basuki Iman Cahyono; Niken Hapsari Arimurti (University of Jember, 2019)
Organic rice farming actually has long been known by rice farmers in Banyumas Regency. Most rice farmers in general are still reluctant to grow organic rice. Most of them still plant non-organic rice, with consideration that they are used to it, the input is easily accessed and obtained, the sales and marketing are easy. Unless there are psychological constraints experienced by farmers there is a concern that using organic fertilizer productivity per land area will decrease, because non-organic rice farmers are accustomed to using inorganic fertilizers who are well aware of the predictions of fertilizer use related to productivity. The research objectives are to 1) determine the role of organic fertilizer on the productivity of organic rice farming; 2) the effect of output prices and input prices on the efficient use of inputs. The research method used was the survey method, the method of determining respondents using a census (number of farmers 39 people). The analytical method uses the financial analysis method, multiple linear regression analysis (Cobb Douglas production function). The results showed that throughout Banyumas District there were only 39 farmers who carried out organic rice farming. Financially, organic rice farming in Banyumas Regency is profitable, with an average profit of Rp.6,698,917, -, with the record that family labor is included as the cost and land is calculated as rent. The addition of seeds, manure, liquid organic fertilizer (POC), organic KCl fertilizer can increase the productivity of organic rice in a row 0.5539%, 0.5339%, 0.1893% and 0.1179% from each additional input of 1%. Addition of pesticides will reduce productivity by 0.1725% from the addition of these inputs by 1%. The effect of output prices and input prices on the efficient use of seed inputs, has been efficient, while the use of manure, and organic KCl and POC have not been efficient and the use of pesticides is inefficient Keyword : efficient, financial, organic, productivity, liquid organic fertilizer